2015
DOI: 10.1364/ol.40.004293
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging of microvascular blood flow networks in deep cortical layers by 1310  nm μODT

Abstract: There is growing interest in new neuroimage techniques that permit not only high-resolution quantification of cerebral blood flow velocity (CBFv) in capillaries, but also a large field of view to map the CBFv network dynamics. Such image capabilities are of great importance for decoding the functional difference across multiple cortical layers under stimuli. To tackle the limitation of optical penetration depth, we present a new ultrahigh-resolution optical coherence Doppler tomography (µODT) system at 1310 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…3D images of microvasculature (ultrahigh-resolution optical coherence angiography-μOCA) and cerebral blood flow networks (ultrahighresolution optical coherence Doppler tomography-μODT) in mouse cortex were reconstructed by speckle variance analysis [22] and phase subtraction method [23], respectively. Although the theoretical image depth of μOCT (z max = λ 2 0 = 4Δλ ð Þ) can be up to approximately 3.6 mm, the measured image depth of μODT for capillary flow network was 1.4 mm [21], which was limited by lens abberrations, depth of field of OCT scan lens and mostly multiple scattering of mouse cortical tissue.…”
Section: In Vivo μOct Surface White Light and Fluorescence Imagingmentioning
confidence: 99%
“…3D images of microvasculature (ultrahigh-resolution optical coherence angiography-μOCA) and cerebral blood flow networks (ultrahighresolution optical coherence Doppler tomography-μODT) in mouse cortex were reconstructed by speckle variance analysis [22] and phase subtraction method [23], respectively. Although the theoretical image depth of μOCT (z max = λ 2 0 = 4Δλ ð Þ) can be up to approximately 3.6 mm, the measured image depth of μODT for capillary flow network was 1.4 mm [21], which was limited by lens abberrations, depth of field of OCT scan lens and mostly multiple scattering of mouse cortical tissue.…”
Section: In Vivo μOct Surface White Light and Fluorescence Imagingmentioning
confidence: 99%
“…So the dispersion effect will limit potential increase of the effective axial resolution with the increase of the bandwidth when the dispersion properties of tissue are taken into account. Recently several groups have constructed FDOCT system with the axial resolution of 1 µm (Liu et al, 2011), 1.27 µm in air (Cui et al, 2014), 3.2 µm in free space (Zhi et al, 2011) and 2.5 µm in brain tissue (You et al, 2015).…”
Section: Effects Of Tissue-induced Dispersionmentioning
confidence: 99%
“…Although optical imaging techniques have been enabling tumor microenvironment studies for decades, a trade-off between speed, depth, and resolution is still the inherent limitation (14). The optical imaging techniques that are proficient in the mesoscopic regime (at a depth of a few millimeters) over the large field of views are limited to either structural imaging (15) or incapable of using readily available conventional fluorescence library (16) [i.e., photoacoustic imaging (PAI)]. Although PAI is highly sensitive against chromophores, recent studies reported fluorescent molecule imaging with newly developed infrared proteins (17).…”
Section: Introductionmentioning
confidence: 99%